Relationship between body mass index (BMI), stage of knee osteoarthritis, and pain severity - Devi, Ninda Callista; Sulistyani; Setiawan, Iwan; Ichsan, Burhannudin (JHeS (Journal of Health Studies), 2024)
The prevalence of knee osteoarthritis has increased significantly over recent decades. Osteoarthritis causes pain, swelling, stiffness, loss of function, and decreased quality of life (QoL). Although evidence suggests that increased BMI contributes to both the development and severity of knee OA, research examining the relationship between BMI, OA stage, and the degree of knee pain remains limited, highlighting the need for further investigation. This study aims to determine the relationship between BMI, the stage of knee osteoarthritis, and the degree of pain in patients with knee OA. This research is an analytical observational study with a cross-sectional design, utilizing secondary data (patient medical records). We conducted sample selection using purposive sampling. Data analysis: descriptive analysis, Chi-Square test, and logistic regression. A total of 101 respondents participated in the study, with the majority had a normal BMI (52.5%), had mild-to-moderate knee OA (56.4%), and reported mild pain (52.5%). There was a significant relationship between BMI and the stage of knee osteoarthritis with the degree of pain (p-value <0.05), with odds ratios (OR) for BMI and OA stage at 3.93 and 3.96, respectively. This indicates that higher BMI and more advanced OA stage are associated with a greater degree of knee pain in patients. Weight loss is an effective strategy to reduce mechanical stress on joints and decrease inflammatory mediators, thereby lowering chronic inflammation and alleviating pain. Further research on effective management strategies for knee OA is essential to help reduce the disease burden and improve the QoL of knee OA patients.